Desain Pompa Air Tenaga Surya Untuk Fasilitas Publik Dengan Software Pvsyst - Vicky Prasetia; Hera Susanti; Muhammad Yusuf; Betti Widianingsih (Infotekmesin, 2025)
Solar energy has great potential as an alternative energy source in Indonesia, but its application for water pump systems in public facilities such as railway stations remains limited. This study aims to design a solar-powered water pumping system (PATS) to meet the water demands at Kroya Station using PVsyst software. The methodology includes site analysis, calculation of daily water requirements, power estimation, and system simulation using PVsyst. The simulation results indicate that the designed system meets 97.5% of the annual water demand of 2,555,000 liters, with a solar panel efficiency of 80.4% and a pump efficiency of 18.5%. The novelty of this study lies in the design of a PATS system for a railway station using simulation-based analysis with PVsyst—an approach not widely applied in public transportation facilities. These findings offer a technical basis for environmentally friendly and sustainable solar pump system planning.